Computer simulation on photoconductivity in hydrogenated amorphous silicon thin films - SH. Chadraabal (Scientific transaction of the National University of Mongolia. Physics, 2022)
Abstract: We used a computer simulation for photoconductivity as a function of temperature in a-Si:H thin films. Utilizing a two level model for photoconductivity, calculated stationary photoconductivity values in a wide range of temperature. The nonlinear differential equations system (1) was solved numerically by iteration technique. For the mobility edge of a-Si:H films, we assumed a model with two level dangling bond centers in the mobility gap. It was shown that the computer modeling results describe well influences of such parameters, as exciting light intensities, capture coefficients for electrons and holes and state densities of dangling bond center levels on behavior of temperature dependence curves of photoconductivity in a-Si:H films.